Codex: A Dual Screen Tablet Computer - Hinckley, Ken; Dixon, Morgan; Sarin, Raman; Guimbretiere, Francois; Balakrishnan, Ravin (CHI '09 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2009)
The Codex is a dual-screen tablet computer, about the size of a 4”x6” day planner, with a self-supporting binding and embedded sensors. The device can be oriented in a variety of postures to support different nuances of individual work, ambient display, or collaboration with another user. In the context of a pen-operated note taking application, we demonstrate interaction techniques that support a fluid division of labor for tasks and information across the two displays while minimizing disruption to the primary experience of authoring notes.